Kompleksitas Persoalan Pasangan Suami-Istri (Sebuah Tawaran Penelitian Pastoral Keluarga Dengan Pendekatan Kualitatif-Induktif) - Bernard H. Pasaribu; Hans H. Purba; Welhelmina S. Manuputty (Jurnal Teologi Cultivation, 2022)
Building a family is a series of processes that require commitment and responsibility from each partner. The fact is that there are many families who are always in conflict and fight, even to the point of divorce. Realizing this, a relevant and contextual hermeneutical study methodology is needed to be able to understand various cases. Through this methodology, each case is reviewed flexibly according to the essence and available information from the case itself. Then this flexibility value will bring up new themes and can be combined into a new substance from the scientific field that is more actual and contextual. Thus, the fruit of this contextual study will help church workers and lay congregations in their efforts to find solutions to problems in the family environment from a broader perspective.